Evaluating HIV-Prevention Programmes: Conceptual Challenges - Campbell, Catherine; Williams, Brian (PINS-Psychology in Society, 2026)
Within the context of HIV prevention in sub-Saharan Africa there is a growing move away from information-based health education towards the development of community-based participatory interventions. This progress has not been matched by the development of conceptual tools and indicators for evaluating the psycho-social and community-level changes which such programmes seek to bring about. Programme evaluators still rely overwhelmingly on individual behavioural and biomedical outcome measures, paying less attention to the processes underlying such outcomes. This paper outlines the rationale and conceptual framework underlying the planned evaluation strategy of a recently implemented three-year HIV-prevention project in the gold mining district of Carletonville. This evaluation seeks not only to measure the extent to which the programme succeeds or fails in having an impact (on levels of HIV and STDs as well as levels of perceived risk and condom use), but also to document the psycho-social and community-level dynamics underlying project outcomes.